THE ORAL QUIZ EFFECT ON STUDENTS SPEAKING SKILL - La Mido (English Education Journal, 2021)
The objective of this research was to know the effect of oral quiz toward students’ speaking ability at the eleventh grade students of SMA Negeri 2 Lakudo. This study is pre-experimental in nature, with a single group pretest and posttest design and no control groups. The participants in this study were eleventh-grade students from SMA Negeri 2 Lakudo, a school with 168 students organized into five classes. The sample of this study was taken by using cluster sampling which consisted of 30 students. The instrument that is used in this research was oral test. The data suggest that oral quizzes have a considerable impact on students' speaking abilities in SMA Negeri 2 Lakudo eleventh grade pupils. The value of t test = 12.39, which was consulted to the t table at a significant level of 0.05 with the standard and degree of freedom (df) = 29, revealed that ttable=1.699. ttest= 12.39 > ttable = 1.699, according to this value. As a result, Ho is denied, whereas H1 is approved. It means that oral quizzes have a big impact on learning English at a higher level.